Rekontruksi Sejarah Lokal sebagai Alternatif Materi Pelajaran Membaca - Dewi, Yusra; Salim, Agus (Universitas Batanghari Jambi, 2022)
This study aims to reconstruct the local history of the â€œPerang Pantaâ€ as an alternative to the reading subject matter. The approach used is a historical and sociological approach to achieve this goal. The research method is a heuristic method. The research data are from reading texts that explain local history in the form of the â€œPerang Pantaâ€ that took place in Nagari Sariak, Agam Regency, West Sumatra Province. The data source is a research report in the form of a scientific paper with the title